YouTube as a virtual springboard: Circumventing gender dynamics in offline and online metal music careers. (1st September 2015) - Berkers, Pauwke; Schaap, Julian
Studies have shown that learning to play in a band is largely a peer-based – rather than individual – experience, shaped by existing sex-segregated friendship networks. With the rise of the Internet and do-it-yourself recording techniques, new possibilities have emerged for music production and distribution. As male-dominated offline metal scenes are often difficult to enter for aspiring female metal musicians, online participation might serve as a possibility to circumvent these gender dynamics. This article therefore addresses to what extent female and male musicians navigate online metal scenes differently, and how this relates to the gender dynamics in offline metal scenes. By conducting ten in-depth interviews with women and men who produce vocal covers on YouTube, this article focuses on the understudied relationship between online and offline scene participation. Vocal covers are used for entertainment, skill development, online skill recognition and as a virtual springboard with which women in particular can (partially) circumvent gender inequality by allowing them to (initially) participate as individuals and pursue musical careers in metal music.